Mucocutaneous Manifestations of Covid-19 in an Isolation Unit of Peshawar, Khyber Pakhtunkhwa - Khan, Abdur Rahim; Gul, Farah; Jalal, Durdana; Haider, Iqbal; Ali Khan, Hamza (Journal of Gandhara Medical and Dental Science, 2023)
OBJECTIVES This study aimed to determine the frequency of mucocutaneous manifestations in patients with COVID-19. METHODOLOGY This prospective cross-sectional study was conducted in the isolation ward of Hayatabad Medical Complex, Peshawar, for COVID-19-positive patients from 20th June to 30th July 2020. One hundred and twenty COVID-19-positive patients were included in our study. Patients fulfilling the inclusion criteria were subjected to a detailed clinical history and mucocutaneous and systemic examination. Relevant investigations were done. Data was recorded in predesigned proforma and analyzed for various statistical variables. RESULTS Among 120 patients included in our study, 87 were male and 33 female. Most patients belonged to the age group 21-40 years. A total of 17 patients showed mucocutaneous manifestations. Generalized pruritus and petechial rash were the most common, and the maculopapular rash were the least common. Mucosal involvement was seen in 2 patients. CONCLUSION Mucocutaneous manifestations are essential clues in the diagnosis of COVID-19. Early recognition may help in the effective management of patients